1997
DOI: 10.1359/jbmr.1997.12.10.1637
|View full text |Cite
|
Sign up to set email alerts
|

Fas and Fas Ligand Interaction Is Necessary for Human Osteoblast Apoptosis

Abstract: We investigated the cellular and humoral interactions between peripheral blood mononuclear cells (PBMCs) and human osteoblasts, leading to apoptosis of osteoblasts. Human osteoblastic cell line MG63 and human primary osteoblast-like cells obtained from biopsy specimens were used in this study. PBMCs were isolated from healthy donors and cultured with or without stimulation by recombinant interleukin-2 followed by 12-o-tetradecanoylphorbol 13-acetate with ionomycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 32 publications
2
51
0
Order By: Relevance
“…46 A predominant pathway of apoptosis in calvarial osteoblasts. 20,21,47,48 and brain 31,[49][50][51] is the Fas mediated pathway. In this pathway, Fas-L activates the Fas receptor to trigger several signaling cascades including Fas-associated death domain (FADD) protein, receptor interacting protein (RIP), or Fas death domain-associated protein (DAXX) and eventually leading to cell death [52][53][54][55][56] Previously, we have reported an upregulation of Fas antigen by overexpression of Nell-1 in MC3T3-E1 osteoblasts in culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 A predominant pathway of apoptosis in calvarial osteoblasts. 20,21,47,48 and brain 31,[49][50][51] is the Fas mediated pathway. In this pathway, Fas-L activates the Fas receptor to trigger several signaling cascades including Fas-associated death domain (FADD) protein, receptor interacting protein (RIP), or Fas death domain-associated protein (DAXX) and eventually leading to cell death [52][53][54][55][56] Previously, we have reported an upregulation of Fas antigen by overexpression of Nell-1 in MC3T3-E1 osteoblasts in culture.…”
Section: Discussionmentioning
confidence: 99%
“…19 Furthermore, in vitro and in vivo studies have demonstrated that signaling through the CD95/ Fas pathway resulted in increases apoptosis in human and murine osteoblasts. [20][21][22] We previously reported the isolation and identification of a novel gene, NELL-1, in human unilateral coronal craniosynostosis (CS) 23 (concurrently identified by Watanabe et al 24 ). NELL-1 is a secretory protein containing 810 amino acids.…”
mentioning
confidence: 99%
“…We examined the expression of pro-caspase-8, procaspase-3, and FasL in cultured thyrocytes by Western blotting as previously described (Kawakami et al, 1997a). In brief, treated thyrocytes were collected and lysed by the addition of lysis buffer (50 mM Tris buffer, pH 8, 150 mM NaCl, 0.02% sodium azide, 0.1% SDS, 100 g/ml PMSF, 1 g/ml of aprotinin, 1% NP-40, 0.5% sodium deoxycholate) for 20 minutes at 4°C.…”
Section: Expression Of Pro-caspase-8 Pro-caspase-3 and Fasl In Cultmentioning
confidence: 99%
“…Briefly, incubated CD4 ϩ T cells with SEB-pulsed thyrocytes were initially reacted with PE-conjugated anti-CD4 mAb (MBL). After incubation, cells were permeabilized with digitonin, as described previously (Anderson et al, 1990;Kawakami et al, 1996), because the polyclonal anti-FasL antibody used in the detection of FasL by flow cytometer recognized the cytoplasmic portion of FasL (Kawakami et al, 1997a;Hakuno et al, 1996, corresponding to amino acids;41-55). After confirming the adequacy of permeabilization by trypan blue uptake, permeabilized cells were incubated with anti-FasL Ab for 30 minutes on ice.…”
Section: Examination Of Thyrocyte Apoptosis In Fratricide or Suicide mentioning
confidence: 99%
See 1 more Smart Citation